أدوار المعلم والقائد التربوي في تأهيل الأشخاص ذوي اضطراب التوحد لسوق العمل من وجهة نظر العاملين في الميدان وأولياء الأمور بمنطقة المدينة المنورة - الشهري، عائشة بنت محمد (مؤسسة التربية الخاصة والتأهيل, 2022)
هدفت الدراسة التعرف على واقع أدوار المعلم والقائد التربوي في مدارس الدمج بهدف التأهيل طلاب التوحد لسوق العمل من وجهة نظر العاملين في الميدان وأولياء الأمور، وعلاقتها ببعض المتغيرات، وتم المنهج الوصفي التحليلي وطبقت الدراسة على عينة مكونة من (١٠٢) من (١٠٢) من العاملين وأولياء طلاب ذوي اضطراب طيف التوحد، واستخدم الباحث استبانة مكونة من (٤١) فقرة موزعة على محورين، وكشفت نتائج الدراسة أن مستوى أدوار المعلم والقائد التربوي في مدارس الدمج بهدف التأهيل طلاب التوحد لسوق العمل جاءت بدرجة مرتفع جدًا مرتفعة بمتوسط (٤,٢٨) وبوزن نسبي (86%) وجاء بعد المهارات الحياتية والاستقلالية أولًا بمتوسط (٤,٣٦) وبوزن نسبي (٨٧%)، يليه بعد الخدمات النفسية والاجتماعية بمتوسط ( ٤,٢٩) وبوزن نسبي (86%) يليه، بعد التدريب المهني بمتوسط (٤,١٨)، وبوزن نسبي (٨٤%).، وكشفت الدراسة عن عدم وجود فروق ذات دلالة إحصائية في تأهيل طلاب التوحد لسوق العمل من وجهة نظر العاملين في الميدان وأولياء الأمور تعزي لمتغير المرحلة الدراسية ودرجة الإعاقة، المؤهل الدراسي للمعلمين وأولياء الأمور وأوصت الدراسة بضرورة الاهتمام بتجهيز الأماكن والأدوات الخاصة بتنفيذ التأهيل المهني، وتوفير ميزانية مناسبة لذلك. The study aimed to identify the reality of the roles of the teacher and educational leader in the integration schools with the aim of qualifying autistic students for the labor market from the point of view of field workers and parents, and their relationship to some variables. The employees and parents of students with autism spectrum disorder, and the researcher used a questionnaire consisting of (41) items distributed on two axes, and the results of the study revealed that the level of the roles of the teacher and the educational leader in the integration schools in order to qualify the autistic students for the labor market came at a very high degree with an average of (4.28) and a weight of ( 86%) and came after life skills and independence first with an average of (4.36) and a relative weight (87%), followed by psychological and social services with an average of (4.29) and a relative weight (86%), followed by, after vocational training with an average of (4.18), (84%) The study revealed that there are no statistically significant differences in the qualification of autistic students in the labor market from the point of view of workers in the field and parents due to the variable of the school stage and the degree of disability, the academic qualification of teachers and parents. Performing professional qualifications, saving forgetfulness and relative weight Adequate budget for it.
Keywords: اضطراب طيف التوحد -- التدخل المبكر -- التدريبات المهنية -- سوق العمل -- معلمو التربية الخاصة -- المحيط الأسري